Giant lipoma of breast-a diagnostic dilemma - Balsarkar, D. J.; Suryawanshi, Sachin A.; Shaikh, Muna; Dhobale, Sudhir (International Surgery Journal, 2021)
Lipoma is the most common benign tumor of adipose tissue. Giant lipoma of breast is very rare.Majority of them are small in size, slow growing and asymptomatic until they reach large size. Most patients seek medical advice due to asymmetry in the breast and due to fear of malignancy. Breast lipomas pose a diagnostic challenge due to similarity of their texture to normal breast parenchyma and make it difficult to distinguish from other common breast lesions. The clinical and radiographic identification of breast lipoma remains challenging. Complete surgical excision with the capsule is essential to prevent recurrence. Breast reconstruction may require, to prevent asymmetry following surgical excision of giant breast lipoma. High degree of clinical suspicion and histolopathological correlation will help in preopertaive diagnosis of this clinical condition. Here, we report a case 50- year -old woman with left breast lump which clinically, radiologically and on fine needle aspiration cytology was diagnosed as phyllodes tumor, but after surgical excision it was reported as breast lipoma on final histopathology.